Self-Perceived Likelihood of False Confession: A Comparison of Justice-Involved Juveniles and Adults - Haney-Caron, Emily (Criminal justice and behavior, 2018)
False confessions represent a significant problem for the criminal and juvenile justice systems and juveniles may be at particular risk for falsely confessing. In part, this risk may be due to juveniles’ greater likelihood of waiving Miranda rights and, consequently, undergoing interrogation, as well as their heightened suggestibility and greater susceptibility to and compliance with authority figures compared to adults. With data from 260 participants in correctional facilities, this study compared juveniles’ (n = 168) and adults’ (n = 92) self-reported likelihood of false confessions. Younger juveniles reported significantly greater false confession propensity than did adults, especially in response to directive interrogation techniques. Older juveniles did not differ significantly from adults in their self-reported likelihood of false confession. Miranda rights comprehension mediated the relationship between age and false confession likelihood. These findings suggest the need for greater protections of younger juveniles during interrogations.